(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The introduction of Islam to India during the Middle Ages caused dramatic shifts in culture. Afterthe immediate rage of the triumphant invaders subsided, the stage was set for communication on severallevels. Alterations were made to buildings, diets, and clothing styles, and even religious practices werealtered. In addition to the many Muslims who were impacted by the tidal wave of the Bhakti movement,many Hindus became students of the Sufis without converting to Islam. Rahim was one of thesepeople.(A.D.1556-1626). Despite being Muslim, he made extensive use of Hindu imagery, including anallegory in which Radha and Krishna serve as a pin to the heavenly spirit. In accordance with a strictreading of the Koran, you must worship and bow down only to Allha. However, Rahim’s lauding of Hindudeities like Krishna, Rama, and Shiva demonstrates that a tolerant environment existed during his time,allowing Rahim to freely communicate his mystical experience. The depth of his knowledge of Hindumythology is evident in his poems. He alludes to tales told in the Puranas. His belief that we can neverknow in what shape we’ll encounter God reflects classic Advita philosophy. The purpose of the proposedarticle is to investigate how the Bhakti movement affected Rahim’s writing.